Socialization of The Role of Ventilators as Medical Support Tools for COVID-19 Patients - Jaya, Indra; Islamy, Fajrul (Research and Social Study Institute, 2023)
Covid-19 is a virus that attacks the lungs so that a person will experience breathing problems. The effect caused by the virus is the thickening of the fluid in the lungs, causing the sufferer to experience difficulty in breathing. This service aim is to socialize and educate the role of ventilators as a medical support tool for COVID-19 patients the general public, students, and Medical staff through webinars. The method used is to provide material online through the Zoom meeting application which is attended by 100 participants using the Zoom application. The results obtained were an increased understanding of the COVID-19 virus and understanding of the functions and benefits of ventilators used for patients as measured based on the pre-test at the start of the webinar with an average value of 63.58 and the post-test held at the end of the webinar with an average value -an average of 91.18 with an increase in understanding of 30.27%. The community is very interested in the material presented and hopes that there will be a continuation of the webinar with other topics.